The transcription factor TCF-1 enforces commitment to the innate lymphoid cell lineage - Harly, Christelle; Kenney, Devin; Ren, Gang; Lai, Binbin; Raabe, Tobias; Yang, Qi; Cam, Margaret C.; Xue, Hai-Hui; Zhao, Keji; Bhandoola, Avinash (Nature immunology, 2019)
Innate lymphoid cells (ILCs) play important functions in immunity and tissue homeostasis, but their development is poorly understood. Through the use of single-cell approaches, we examined the transcriptional and functional heterogeneity of ILC progenitors, and studied the precursor–product relationships that link the subsets identified. This analysis identified two successive stages of ILC development within T cell factor 1-positive (TCF-1 + ) early innate lymphoid progenitors (EILPs), which we named ‘specified EILPs’ and ‘committed EILPs’. Specified EILPs generated dendritic cells, whereas this potential was greatly decreased in committed EILPs. TCF-1 was dispensable for the generation of specified EILPs, but required for the generation of committed EILPs. TCF-1 used a pre-existing regulatory landscape established in upstream lymphoid precursors to bind chromatin in EILPs. Our results provide insight into the mechanisms by which TCF-1 promotes developmental progression of ILC precursors, while constraining their dendritic cell lineage potential and enforcing commitment to ILC fate. Bhandoola and colleagues show that the transcription factor TCF-1 restrains the dendritic cell lineage potential in innate lymphoid cell progenitors.